Pegada hídrica como indicador de sustentabilidade ambiental em sistemas de produção agrícola na Amazônia - Costa, Douglas Cavalcante (2017)
This research aimed to assess the water footprint as an indicator of environmental sustainability in agricultural production systems in the Amazon. The methodology developed in Holland gained adoption and has been tested in various regions of the planet as a strategy to account for how much water has been used in the production of goods, products, or services. As the Brazilian Amazon holds large freshwater reserves on Earth, this dissertation was structured considering this indicator of water consumptive use as follows. Chapter 1 presents a brief theoretical framework of the methodology and how this knowledge was approached focusing on water footprint (WF) as an indicator based on a logical diagram of agricultural production sustainability in the Amazon. Chapter 2 features a literature survey of the scientific production that applied the water footprint methodology to assess the responsible use of water to offer a given product. The literature survey in Brazilian and international journals between 2006 and 2016 yielded 13,085 papers, but, in Brazil, only 3% of the studies employed WF as an indicator of use of this important natural resource that is water, while four papers were carried out with data on water use in the Brazilian Amazon. Chapter 3 tallied the water footprint in the 2013/2014 harvest year of the most commonly planted soybean (Glycine max) cultivars in the grain center of Paragominas, northeast state of Pará. Pluvial and phenological data of a field experiment of Embrapa were used and agrometeorological assessments were performed during harvest with a sampling unit installed at the soybean experiments carried out by Embrapa at Poderosa farm. The total water footprint in that harvest in Paragominas ranged from 1,015 m3 ton-1 to 1,306 m3 ton-1 . vi Chapter 4 analyzes the temporal dynamics of the water footprint of eight soybean cultivars in the grain center of Santarém, west state of Pará. The evapotranspiration rates were estimated based on the meteorological data available from 2009 to 2014 and on mean phenological data of the cultivars available in the literature for the region, such as China. The mean water footprint estimated for soybean grown in the Santarém/Belterra grain center was lower than the valued obtained by researchers in other countries. For instance, the water footprint was about 30% below the results of that indicator for soybean crops in China. It is worth pointing out that, in the grain center in west Pará, the WF was 5% lower than the values reported in studies on databases of the grain center of Paragominas. Moreover, the soybean grown in Santarém/Belterra has a smaller water footprint than the global average, whose values are 41% higher than those obtained in this research. It is concluded that there are soybean cultivars with great potential to be used in grain crops for their high water use efficiency in a given harvest year. Therefore, the decision to sow one cultivar in the grain centers of the Amazon may be subsidized by the WF values as a strategy to reduce consumptive water use in agriculture due to the high evapotranspiration efficiency with a reduction in green water footprint since it indirectly expresses the high yields of a given cultivar compared to the other cultivars available in the region. It is concluded that WF is an excellent indicator of consumptive water use in the agricultural production systems in the Amazon since, in terms of efficient water use, this indicator expressed lower values compared to the global average